Poems for travellers - Morgan, Gaby (Macmillan Collector's Library, 2019)
"As internationally acclaimed author Paul Theroux writes in his introduction, 'Here is a collection of travel poetry composed by real travellers, weekending tourists, feverish fantasists, bluffers, dreamers, brave adventurers and resolute stay-at-homes. It succeeds in what poetry does best -- inspires and consoles, reminds us of who we are, where we've been, and where we might want to go next.'"--Amazon.con.